2010
DOI: 10.1128/jcm.01326-10
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes and Staphylococcus epidermidis Isolated from Refractory Endodontic Lesions Are Opportunistic Pathogens

Abstract: The predominant cultivable microbiota from 20 refractory endodontic lesions (9 with abscesses and 11 without abscesses) were determined, and Propionibacterium acnes and Staphylococcus epidermidis were among the most predominant organisms. The number of species identified from lesions with abscesses (14.1 ؎ 2.6) was significantly greater (P < 0.001) than the number from lesions without abscesses (7.4 ؎ 5.9). Comparison of perioral isolates using repetitive extragenic palindromic PCR of the same species from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 65 publications
(54 reference statements)
3
86
1
Order By: Relevance
“…Data collated from three different studies have demonstrated that amongst 203 P. acnes isolates from the facial skin of 64 volunteers, type IA (~50 %) and IB (~40 %) organisms are the dominant lineages present (Shannon et al, 2006;Holmberg et al, 2009;Niazi et al, 2010). The absence of type IB strains amongst acne isolates despite their presence on facial skin provides evidence that type IA-specific factors are responsible for the association with acne.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collated from three different studies have demonstrated that amongst 203 P. acnes isolates from the facial skin of 64 volunteers, type IA (~50 %) and IB (~40 %) organisms are the dominant lineages present (Shannon et al, 2006;Holmberg et al, 2009;Niazi et al, 2010). The absence of type IB strains amongst acne isolates despite their presence on facial skin provides evidence that type IA-specific factors are responsible for the association with acne.…”
Section: Discussionmentioning
confidence: 99%
“…Caveats associated with aspects of previously described single locus phylotyping of P. acnes were highlighted upon validation of the MLST approach. All strains of type IB contain a GAA polymorphism at position 897 in the recA open reading frame which has been widely used to conveniently differentiate this group from type IA strains Shannon et al, 2006;Holmberg et al, 2009;Sampedro et al, 2009;Niazi et al, 2010). While this polymorphism appears sensitive for type IB STs, it is not specific since strains confirmed as type IA by MLST were also found to occasionally share this particular recA allele.…”
Section: Discussionmentioning
confidence: 99%
“…P. acnes, an opportunistic pathogen in refractory endodontic infection, may be associated with contamination of dental materials during the root canal filling procedure and has been isolated from infected root canals [16]. This species has been found to have high sensitivity to essential oil components that may adhere to the bacterial surface at low concentration [57].…”
Section: Discussionmentioning
confidence: 99%
“…E. faecalis, in particular, is difficult to remove owing to its considerable virulence factors constituting a source of recurrent infection after conservative as well as surgical treatments [15]. P. acnes is an anaerobic Grampositive bacterium responsible for a wide range of infections and inflammatory conditions [16]. Therefore, development of antibacterial restorative filling materials to be reliable for a variety of dental applications need a potent antimicrobial agent which acts against a wide range of oral microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Of the total, opportunistic pathogens (Staphylococcus spp. (Niazi et al, 2010) (4%)) were identified.…”
Section: Matrix Assisted Laser Desorption Time Of Flightmentioning
confidence: 99%